Solvation structure around the Li+ ion in succinonitrile–lithium salt plastic crystalline electrolytes. Issue 22 (18th May 2016) - Shen, Yuneng; Deng, Gang-Hua; Ge, Chuanqi; Tian, Yuhuan; Wu, Guorong; Yang, Xueming; Zheng, Junrong; Yuan, Kaijun
Abstract : The FTIR spectra and rotation decay of pure SN and Li–SN complex in LiBF4 /SN solutions. Abstract : Herein, we discuss the study of solvation dynamics of lithium–succinonitrile (SN) plastic crystalline electrolytes by ultrafast vibrational spectroscopy. The infrared absorption spectra indicated that the CN stretch of the Li + bound and unbound succinonitrile molecules in a same solution have distinct vibrational frequencies (2276 cm −1 vs. 2253 cm −1 ). The frequency difference allowed us to measure the rotation decay times of solvent molecules bound and unbound to Li + ion. The Li + coordination number of the Li + –SN complex was found to be 2 in the plastic crystal phase (22 °C) and 2.5–3 in the liquid phase (80 °C), which is independent of the concentration (from 0.05 mol kg −1 to 2 mol kg −1 ). The solvation structures along with DFT calculations of the Li + –SN complex have been discussed. In addition, the dissociation percentage of lithium salt was also determined. In 0.5 mol kg −1 LiBF4 –SN solutions at 80 °C, 60% ± 10% of the salt dissociates into Li +, which is bound by 2 or 3 solvent molecules. In the 0.5 mol kg −1 LiClO4 –SN solutions at 80 °C, the salt dissociation ratio can be up to 90% ± 10%.